Pediatric Palliative Care. Issue 1 (13th October 2021) - Moresco, Benjamin; Moore, Dominic
ABSTRACT: Objective/Methods: Pediatric Palliative Care (PPC) is a multidisciplinary medical subspecialty focused on the care of children with serious illnesses and terminal diagnoses. Providers impact the care of children from the perinatal stage through adolescence/young adulthood and help patients and families face diagnoses such as complex chronic disease and malignancy. This article describes these unique populations and distinct areas of current PPC research. Results: Unique aspects of PPC include a high level of prognostic uncertainty, symptom burden, pediatric, and surrogate advance care planning, hope in the face of prognostic challenges, care of children at end of life, concurrent care, staff support, sibling support, and bereavement. Conclusion: PPC's evolution from an extension of hospice into a continuum of support for families and staff caring for children with serious illnesses is exemplified in both qualitative and quantitative research. The literature proves the value that PPC can provide to families, hospitals, and communities. PPC is evolving from a supportive service into a uniquely beneficial, collaborative, educational, and interdisciplinary specialty that improves outcomes for all involved. Plain Language Summary (PLS) Pediatric Palliative Care (PPC) is a service provided to all children with serious illness as a way of addressing suffering. Populations served by PPC range from those not yet born to patients preparing for adulthood. The serious illnesses they face range from chronic disease to cancer. Over the last 20 years research has explored the unique aspects of the pediatric experience of serious illness, including prognostic uncertainty, concurrent care, symptom management, advance care planning, hope, family experience of illness, care at the end of life, staff support, and bereavement. As the number of patients who would benefit from PPC services rapidly expands nationally and worldwide, PPC teams provide education and skills training for their colleagues in primary and subspecialty fields. Hospitals benefit from PPC through improved patient experience, family-centered care, and staff support. Communities are served by PPC that occurs in and out of the hospital. Research in PPC provides guidance for challenging questions in care and has resulted in an increasingly robust body of work. PPC providers have skills of advanced communication training, hope in the face of uncertainty, targeted and personalized symptom management, and a diverse understanding of quality of life. These skills help support decision-making and establish strong connections between providers and families. The field of PPC has a distinct skillset to support families who face serious illness. This article helps medical and psychosocial providers visualize how PPC is evolving from what has often been explained to families as an added layer of support into a uniquely beneficial, collaborative, and interdisciplinary service.